Pedagogical Innovation in Primary Education: A Comparative Analysis of Teaching Practices in Public and Private Schools - Ramsha Rashid*; Aqsa Arif; Anam Rana; Shumaila Zafar; Aqsa Ijaz; Zafar Iqbal; Ghazanfar Ali Khan; Aqeela Saghir; Muhammad Iftikhar (`, 2025)
This study explores the comparative implementation of pedagogical skills and teaching methodologies in public and private primary schools of Faisalabad, Pakistan. With the growing emphasis on educational quality and student engagement, the research aims to examine how teachers from both sectors apply instructional strategies, manage classrooms and utilize modern teaching techniques in their daily practices. Using descriptive-comparative model with inferential analysis, data were collected through a structured questionnaire from a sample of 120 primary school teachers, evenly divided between public and private institutions. The findings reveal significant disparities between the two sectors. Private school teachers were more inclined toward the use of student-centered approaches, ICT integration and innovative classroom practices, whereas public school teachers, despite holding higher academic qualifications, faced challenges such as lack of resources, overcrowded classrooms and limited professional development opportunities. The study concludes that teacher effectiveness is shaped not only by formal education but also by institutional support, training availability, and access to pedagogical tools. Recommendations include targeted policy reforms, increased investment in teacher training and enhanced collaboration between public and private educational institutions to bridge the pedagogical implementation gap. Keywords: Pedagogical Skills, Teaching Methodologies, Public Schools, Private Schools, Primary Education, ICT Integration, Teacher Training, Comparative Study